The Main Tendencies of Hungarian Legal Historiography in the 20th Century and its Present Situation - István Stipta (Journal on European History of Law)
The essay analyses first the Hungarian legal historiography in the 20th century. It gives the list of scientific schools of the Horthy era and its most important representatives. In addition, the essay examines the intellectual impacts that shaped the contemporary science of Hungarian legal history. After then, the paper deals with the so called socialist science appearing after World War II. The essay refers to the ideological subjection (determination) of the science and the battle of the old and new approach. The chapter that introduces the present situation of the science of legal history displays the research centers of legal history reawakening from the 1970’s. The paper also reviews the process of development of the education and research centers in the provinces. It also introduces the procedure of how the science of history and legal history approached each other. The author endeavors to name each important scholar and to refer to the most remarkable works written by those.